TISSUE AROMA TERAPI “UPIK ABU” (UNTUK PENYELAMAT BUMI KITA TERBUAT DARI AMPAS TEBU) - Nuraini Fauziah; Novita Istikhomah; Exwan Andriyan; Andina Puspawati (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractEntrepreneurship Student Creativity Program of "Upik Abu" Tissue (made fromsugar cane dregs to save the earth) is in response to the increasing need for tissues. Itis also motivated by the intention to produce tissues without cutting down trees as aneffort to save the environment, as well as to use of the cane pulp which is usually onlyused as fuel for locomotives. This program is aimed to: (1) produce Aroma TherapyTissue, (2) develop a marketing strategy, and (3) get the sales profit. This activityincludes producing tissues through a cooperation with partners, introducing, andselling products of "Upik Abu" tissues. The implementation stage includes theactivities of market surveys and production. The market survey is conducted to get anoverview of market potencial. The production process consists of three stages, namelypreparation, execution, and finishing. The tissues are produced in the form of facialtissues, toilet tissues, and tissues at the dinner table. The process of marketing is donethrough printed media (business cards, leaflets, mass media), electronic media(facebook, twitter, blogs, SMS), community, exhibition, and consignment with somegrocery stores. Aroma therapy is added to the tissue to be more marketable as well ascomfortable to use. Tissue production has reached 650 units, with sales profit forthree months of 3,862,500 rupiahs. Based on the results obtained it can be concludedthat the business is profitable, so the continuity of business will continue to bemaintained, along with the efforts to increase profits.